Effect of Agro Waste Particles on the Mechanical Properties of Hybrid Unsaturated Polyester Resin Matrix Composites - Durowaye, Stephen; Sekunowo, Olatunde; Kuforiji, Catherine; Nwafor, Chiemelie; Ekwueme, Chidiebere (Journal of the Institute of Engineering, 2019)
The efficacy of reinforcement of polyester resin matrix composites with agro waste particles to effect improvement on the disadvantage of low mechanical properties for optimal performance was studied. 5-25 wt. % of coconut shell, periwinkle shell, and cow bone particles were applied in reinforcing unsaturated polyester resin matrix by mould casting and the microstructural and mechanical characteristics of the composites were evaluated. There was uniform distribution of the agro waste particles in the polymer composites matrix from the scanning electron microscopy (SEM) result. The hybrid composite at 15 wt. % reinforcement demonstrated the highest mechanical properties in terms of ultimate tensile strength (66.73 MPa), flexural strength (76.76 MPa), hardness (87.76 BHN), and impact energy (23.16 J). This shows the efficacy of hybridisation and the high potential of the composite for wider applications.